2018
DOI: 10.1103/physrevc.98.015205
|View full text |Cite
|
Sign up to set email alerts
|

NΩ interaction: Meson exchanges, inelastic channels, and quasibound state

Abstract: Based on a baryon-baryon interaction model with meson exchanges, we investigate the origin of the strong attraction in the N Ω( 5 S2) interaction, which was indicated by recent lattice QCD simulations. The long range part of the potential is constructed by the conventional mechanisms, the exchanges of the η meson and of the correlated two mesons in the scalar-isoscalar channel, denoted by "σ" in the literature. The short range part is represented by the contact interaction. We find that the meson exchanges do … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 81 publications
1
23
0
Order By: Relevance
“…4 (Left) is the 1 S 0 potential V LO 0 (r) for t/a = 11−14. These potentials are consistent with each other within statistical errors, which is an indirect evidence of the small coupling with the D-wave octet-octet states below the NΩ threshold in the spin-2 channel as suggested in [23]. (Such a stability of the potential in the same range of t is not found for the spin-1 NΩ system which can couple to the S-wave octet-octet states below threshold.)…”
Section: ωω and Nω Interactionssupporting
confidence: 76%
“…4 (Left) is the 1 S 0 potential V LO 0 (r) for t/a = 11−14. These potentials are consistent with each other within statistical errors, which is an indirect evidence of the small coupling with the D-wave octet-octet states below the NΩ threshold in the spin-2 channel as suggested in [23]. (Such a stability of the potential in the same range of t is not found for the spin-1 NΩ system which can couple to the S-wave octet-octet states below threshold.)…”
Section: ωω and Nω Interactionssupporting
confidence: 76%
“…The statistics are slightly improved from the result at the conference 2. The effect of these coupling channels is found to be small from the phenomenological study in Ref [11],. nevertheless, the coupled channel analysis would be required to confirm this assumption in the future[3].…”
mentioning
confidence: 59%
“…Recently, the model-independent studies of the H-dibaryon are reported from lattice QCD calculations [2,3,4]. Due to the absence of the Pauli blocking effect, another promising candidate for the dibaryon is NΩ(uudsss or uddsss), which is claimed to be bound from the studies based on the phenomenological models [5,6,7,8,9,10,11]. This dibaryon is also reported from the (2+1)-flavor lattice QCD study for the heavier pion mass at m π 875 MeV [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the existence of the dibaryon is still controversial. In recent years, the theoretical and experimental studies of dibaryon states have been extended to systems containing more strangeness quarks [60][61][62][63][64][65][66][67][68][69][70][71][72].Experimental searches for dibaryons containing charm quarks is challenging because of the high energy required and the low production of charmed baryons. On the other hand, many theoretical studies have been performed.…”
mentioning
confidence: 99%
“…However, the existence of the dibaryon is still controversial. In recent years, the theoretical and experimental studies of dibaryon states have been extended to systems containing more strangeness quarks [60][61][62][63][64][65][66][67][68][69][70][71][72].…”
mentioning
confidence: 99%